Upaya Nation Branding Pariwisata dalam Kepentingan Singapura melalui penyelenggaraan KTT A.S-Korea Utara tahun 2018 - Mega Pratama, Anak Agung Ayu Regina; Priadarsini, Ni Wayan Rainy; Kawitri Resen, Putu Titah (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2019)
ABSTRACT This research aims to describe the Singapore Government's efforts to promote Singapore Tourism using the nation branding method by holding a U.S.-North Korea Summit which spent US$20 million. The more advanced competitors in the field of tourism, namely MICE, triggered Singapore to conduct branding using media coverage. However, the benefits of Singapore are estimated to be not only short-term benefits but long-term benefits. Therefore, the Researcher used the Nation Branding and International Image framework to explain Singapore's efforts to achieve a tourism marketing strategy through the holding of the U.S.-North Korea Summit. The Research then perceives the answer, that Singapore made a nation branding effort through a controversial event with the help of media coverage to target a broader market and the contribution of non-governmental actors.    Keyword: Nation Branding, Citra Internasional, MICE, KTT A.S-Korea Utara.